Incidencia de diabetes y obesidad en la población del cantón Paltas y su relación con el estilo de vida - Saritama Gallegos, Kevin Rolando (2022)
Diabetes and obesity are a group of non-communicable diseases that are among the leading causes of morbidity and mortality worldwide where in 2019 caused 1.5 million deaths and a prevalence of overweight of 39% and obesity with 13%. Therefore, the present research work aims to determine the incidence of diabetes and obesity in the 3 population of the canton of Paltas and its relationship with lifestyle in the period MarchApril 2022, the research had a non-experimental quantitative approach and longitudinalcorrelational cut, consisting of 175 participants. The results obtained showed that 18.9% (N=33) had elevated glucose, 32.0% (N=56) were overweight and 11.4% (N=20) obese, statistically using the Chi-square test, no relationship was found between the risk factors and the disease, the age with the highest frequency for both elevated glucose and cholesterol was 70 to 79 years with 27.3% (N=9) and 26.3% (N=2) and 26.4% (N=3) respectively, 3% (N=9) and 26.9% (N=7) respectively, while for triglycerides it was from 30 to 39 years with 23.6% (N=21), the male sex had a higher frequency according to elevated glucose and cholesterol values with 14.9% (N=9) and 14.9% (N=7) respectively, triglycerides had a predominance of the female sex with 55.5% (N=71). It can be concluded that of the 175 participants, 18.9% (N=33) presented hyperglycemia which were considered as possible cases to develop type 2 diabetes mellitus, 32% (N=56) were overweight and 11.4% (N=20) obese, Furthermore, there is no relationship between the factors associated with lifestyle and the disease, but the total of the survey showed that both patients with hyperglycemia and obese patients have an unhealthy lifestyle with 84.8% (N=28) and 85.0% (N=17) respectively